2018
DOI: 10.1177/1751143718804678
|View full text |Cite
|
Sign up to set email alerts
|

Using a CriSTAL scoring system to identify pre-morbid conditions associated with a poor outcome after admission to intensive care in people 70 years or older

Abstract: Older people admitted to intensive care are considered to have lower physiological reserves, an increased susceptibility to infection and longer recovery times, resulting in generally poorer outcomes after intensive care treatment. However, biological heterogeneity makes identification of those with the best chances of survival within their group difficult and risks subjecting those at the end of their lives to unsuccessful treatments. There is no fit-for-purpose outcome prediction tool capable of identifying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…A modified version of CriSTAL tested in the United Kingdom also found that metastatic cancer and Rockwood's frailty were significant predictors of death among older patients in intensive care . Our findings are also consistent with those of another prospective study in Dutch EDs, where cognitive impairment was associated with physical decline and 90‐day mortality (AUROC = 0.79, 95% CI = 0.73–0.85) .…”
Section: Discussionsupporting
confidence: 89%
“…A modified version of CriSTAL tested in the United Kingdom also found that metastatic cancer and Rockwood's frailty were significant predictors of death among older patients in intensive care . Our findings are also consistent with those of another prospective study in Dutch EDs, where cognitive impairment was associated with physical decline and 90‐day mortality (AUROC = 0.79, 95% CI = 0.73–0.85) .…”
Section: Discussionsupporting
confidence: 89%
“…For this purpose, Boumendil et al [22] used the Knauss classification [78] as based on physiological parameters. Some studies included cognition in their functional assessment, by using the Short Portable Mental Status Questionnaire (SPMSQ) [21] or Folstein's MMS [19], the cognitive score as component of Lawton-Brody IADL scale [23], the Informant Questionnaire on Cognitive Decline in the Elderly (IQCODE) [10,34,46], the Clinical dementia rating scale (CDR) [47], or the Cognitive Performance Scale (CPS) [58]. Two studies added the nutritional status [27,47].…”
Section: Methods Of Frailty Assessment In the Critically Ill Andmentioning
confidence: 99%
“…Eight studies (17%) established a frailty diagnosis based on their own criteria [10,21,33,45,[59][60][61]79] -4 of them exclusively [21,60,61,79] -but the others in combination with established scores. The most common criterion was a combination of decreased cognitive function and functional status and disability in daily life, with the exception of Ball et al [79] who only referred to phys-Gerontology 2022;68:1321-1349 DOI: 10.1159/000523674 iological parameters.…”
Section: Methods Of Frailty Assessment In the Critically Ill Andmentioning
confidence: 99%
See 2 more Smart Citations